2014
DOI: 10.1002/ece3.989
|View full text |Cite
|
Sign up to set email alerts
|

Filling the gap in functional trait databases: use of ecological hypotheses to replace missing data

Abstract: Functional trait databases are powerful tools in ecology, though most of them contain large amounts of missing values. The goal of this study was to test the effect of imputation methods on the evaluation of trait values at species level and on the subsequent calculation of functional diversity indices at community level using functional trait databases. Two simple imputation methods (average and median), two methods based on ecological hypotheses, and one multiple imputation method were tested using a large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 51 publications
1
96
0
3
Order By: Relevance
“…Even if Mean imputations imply the rather naive assumption that species identity may be unknown in a given dataset, it is nonetheless useful to compare Mean imputations against mice and kNN, which use the full trait matrix for prediction. In this case, trait covariation did not improve imputations at high missingness; recent assessments also report that the performance of MICE and kNN notably declines when missingness is ≥ 30 % (Penone et al, 2014;Taugourdeau et al, 2014). Therefore, our results for OrdKrig, compared to those for mice and kNN, show that spatial structure, rather than trait covariation, may provide more accurate trait imputations when gaps are frequent (Fig.…”
Section: Mean Imputations Compared To Mice and Knn Imputations Usingmentioning
confidence: 45%
See 3 more Smart Citations
“…Even if Mean imputations imply the rather naive assumption that species identity may be unknown in a given dataset, it is nonetheless useful to compare Mean imputations against mice and kNN, which use the full trait matrix for prediction. In this case, trait covariation did not improve imputations at high missingness; recent assessments also report that the performance of MICE and kNN notably declines when missingness is ≥ 30 % (Penone et al, 2014;Taugourdeau et al, 2014). Therefore, our results for OrdKrig, compared to those for mice and kNN, show that spatial structure, rather than trait covariation, may provide more accurate trait imputations when gaps are frequent (Fig.…”
Section: Mean Imputations Compared To Mice and Knn Imputations Usingmentioning
confidence: 45%
“…Stochasticity is introduced in the imputation process because the parameters of the univariate imputation models are drawn from their posterior distributions, obtained using a Gibbs sampler (van Buuren, 2012). Assessments of imputation methods in the ecological literature have not tested the impact of the choice of univariate imputation models within MICE (Penone et al, 2014;Taugourdeau et al, 2014). Here we showed that predictive mean matching (PMM), the default algorithm in the mice package, performed well compared to alternative methods (Sect.…”
Section: Imputation Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Trait proximity was previously shown to perform well in imputation of missing data in the assessment of functional diversity indices (Taugourdeau et al. 2014). We chose six species as a compromise between having variability in extinction risks and because the method was less powerful when we chose a higher number of species more different in range size (Appendix S4).…”
Section: Methodsmentioning
confidence: 99%